Epidemiology and aetiology of bruxism in children and adolescents – review of literature - Dąbrowska - Gontarczyk, Anna; Syczewska, Małgorzata; Jelonek, Elżbieta; Graff, Krzysztof; Zadurska, Małgorzata; Kalinowska, Małgorzata; Szczerbik, Ewa; Olczak - Kowalczyk, Dorota (Journal of Stomatology, 2015)
Introduction. Many publications suggest that bruxism is one of the most common parafunctional habits. Aim of the study. To review reports in literature in order to assess the prevalence and potential causes of bruxism in children and teenagers. Materials and methods. Randomised, cohort, and case-control studies on groups of more than one hundred people between 2000-2012 were qualified to assess bruxism occurrence in children and adolescents. Case studies and articles published in other languages than Polish and English were excluded. Four hundred and nineteen publications were encountered, of which fifty met the inclusion criteria. Results. The prevalence of bruxism in patient groups determining the dentition type varied from 2.1 to 55.3%. Bruxism may have psychological, emotional, and neurological causes; it may also result from systemic diseases or local factors. Conclusion. The literature review revealed that bruxism is one of the most common parafunctional habits of multifactorial aetiology that still requires better understanding.